Seasonal and diel vertical migration of zooplankton in the High Arctic during the autumn midnight sun of 2008 - Rabindranath, Ananda; Daase, Malin; Falk-Petersen, Stig; Wold, Anette; Wallace, M.I.; Berge, Jørgen; Brierley, A. S. (Marine Biodiversity, 2011)
This article is part of Anette Wold's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/4152 The diel vertical migration (DVM) of Calanus (Calanus finmarchicus, Calanus glacialis and Calanus hyperboreus) and Metridia longa was investigated in August 2008 at six locations to the north and northwest of Svalbard (Rijpfjorden, Ice, Marginal Ice Zone, Shelf break, Shelf and Kongsfjorden). Despite midnight sun conditions, a diel light cycle was clearly observed at all stations. We collected data on zooplankton vertical distribution using a Multi Plankton Sampler (200-μm mesh size) and an EK60 echosounder system (38, 120 and 200 kHz). These were supplemented by environmental data collected using a standard conductivity, temperature and depth (CTD) profiler. The sea ice had recently opened in Rijpfjorden, Ice and Shelf stations, and these stations exhibited phytoplankton bloom conditions with pronounced fluorescence maxima at approximately 30 m. In contrast, Kongsfjorden was more representative of autumn conditions, with the Arctic bloom having culminated 2–3 months prior to sampling. All three Calanus species were found shallower than 50 m on average at Rijpfjorden and the Ice station, while C. glacialis and C. hyperboreus were found deeper than 200 m on average at Kongsfjorden. Shallow water DVM behaviour (<50 m) was observed at Rijpfjorden and the Shelf station, especially among the C. finmarchicus CI-CIII population, which was particularly abundant at the Shelf (>5,000 individuals/m3). A bimodal depth distribution was observed among C. finmarchicus at the Shelf break station, with CI-CIII copepodites dominating at depths shallower than 100 m and CIV-adult stages dominating at depths exceeding 600 m. Statistical analyses revealed significant differences between the day and night 200-kHz data, particularly at specified depth strata (25–50 m) where backscatter intensity was higher during the day, especially in Rijpfjorden and at the Ice station. We conclude that DVM signals exist in ...